Modification of implementation of group guidance service in improving the quality of guidance and counseling service for school students - Neviyarni, Neviyarni (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
The aim of this study was to analyze and interprete the previews studies about modification of implementation of group guidance service. The researcher was conducted this study using qualitative approach which involved case study’s strategy. According to those post graduate student’s findings, the researcher intended to find: (1) what were modifications that done, (2) how were they happened, (3) why were they happened, (4) how were the results, (5) how were the effectively of its effects, (6) how were the possibilities of its implementation in the future. The findings of this study were the average score results of implementation of group guidance with modification has better score than the avarage score results in implementation of group guidance service without modification, Suggestion in developing learning discipline, Bibliotherapy in enhacing self-concept. Suggestion in developing learning discipline, Bibliotherapy in enhacing self-concept, Modifications in this study was conducted by Role Playing to improve self-adaptation, Verse of Holy Al-Qur’an to improve learning motivation, Audio Visual Media to improve self concept, Assertive Training to improve interpersonal communication, REBT eliminates affraid, Modeling to improve Self Efficacy, Reality Counseling to develop self-adaptation. Regarding to this, it is hope for Guidance and Counseling teachers/ Counselors to improve the quality of service with implementation of group guidance service through several modifications.